Equação do transporte em sistema de águas rasas - Kurz, Gustavo Braz (2024)
This dissertation aims to implement a method for solving the transport equation in shallow water systems using a flow simulation program. The chosen method involves finite element discretization using the Galerkin method. More specifically, a code is developed to simulate the flow, employing the method of characteristic-based split (CBS). Spatial discretization is performed using linear triangular finite elements. The dissertation also includes a series of studies to validate the methodology, covering well-established problems in the literature on shallow water flow. Additionally, additional investigations are conducted to study the dispersion of pollutants in the body of water, including scenarios of greater complexity.